التنظيم القانوني لعقد العمل تحت التجربة )دراسة تحليلية- مقارنة( - م.م.كيفي مغديد قادر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Our Research is about a very special kind of labor contract, which has a good implementation in real under the title a "labor contract under test" in which we tried to explain all the legal aspects related to the subject. In the first part, we tried to give a definition to the contract, by analyzing the contain of it and focusing on its essential elements. But in the second part, we gave a legal adaptation to the contract through putting down all the Jurisprudence theories which exist on the contract, above that, we intend to show the point of view of the Iraqi labor court and all the comparative labor courts, by analyzing more than one labor court decisions, to find out its positive and negatives. While in the third and last part of our research, we focused on all the legal provisions which are specialized to this type of labor contract only, namely the subject of finishing the contract and the duration of it. We ended the research by collecting all the reached results and providing more than one recommendation, which we hope it service, our society and legal study in general.